VD_FINDINFO 2/2010/PHC vom 22. Dezember 2009 - VD Tribunal cantonal (2009)
ACTION EN RÉVOCATION, ACTION RÉVOCATOIRELP, SURENDETTEMENT, EXÉCUTION FORCÉE, LÉGITIMATION ACTIVE ET PASSIVE | 74 LOJV, 285 LP, 286 LP, 287 LP, 288 LP, 289 LP, 290 LP, 291 LP, 42 LVLP